Pengembangan Instrumen Tes Diagnostik Tiga Tingkat dan Alternatif Remedial pada Pembelajaran Kimia - Asmalinda, Asmalinda; Ruslan, Ruslan; Sulastry, Taty (Chemistry Education Review (CER), 2019)
This study is research and development, which aims at developing diagnostic test instrument on atomic structure material. The research subjects were the students of grade X MIPA 3 at SMAN 22 Makassar with 34 respondents  consisted of 15 male students and 19 female students. The procedure of instrument development adopted ADDIE development model which covered several stages, namely analysis, design, development, implementation, and evaluation. The results of the study reveal that the validity of instrument is 1 or V= 100%, meaning that assessment from boths have strong relevancy and the result of SPSS version 23.0 also indicates that the instrument is in valid category. The result on SPSS also obtain Cronbach’s Alfa 0.872 (reliable category); whereas, the objectivity is determined based on the agrrement of both expect which reveal that the result is in objective category. The remedial can be conducted using drill method for calculation question the leaning method uses the media in a form of a video for theoretical questions.